2015
DOI: 10.1371/journal.pone.0137655
|View full text |Cite|
|
Sign up to set email alerts
|

RootAnalyzer: A Cross-Section Image Analysis Tool for Automated Characterization of Root Cells and Tissues

Abstract: The morphology of plant root anatomical features is a key factor in effective water and nutrient uptake. Existing techniques for phenotyping root anatomical traits are often based on manual or semi-automatic segmentation and annotation of microscopic images of root cross sections. In this article, we propose a fully automated tool, hereinafter referred to as RootAnalyzer, for efficiently extracting and analyzing anatomical traits from root-cross section images. Using a range of image processing techniques such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…The GRANAR model generates cell networks of root cross sections from a small set of root anatomical features ( 23 . Briefly, the anatomy generation process is based on the placing of cell layers around the center of the root.…”
Section: Resultsmentioning
confidence: 99%
“…The GRANAR model generates cell networks of root cross sections from a small set of root anatomical features ( 23 . Briefly, the anatomy generation process is based on the placing of cell layers around the center of the root.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variation in rice root traits has been reported such as root thickness (Babu et al, 2001) and deep rooting (Nemoto, Suga, Ishihara & Okutsu, 1998), and the latter has been shown to be useful for drought avoidance (Kato et al, 2007;Yoshida & Hasegawa, 1982) and for watersaving (Deshmukh, Kamoshita, Norisada & Uga, 2017) to lead to higher yield (Uga et al, 2013). However, studies of root anatomical traits are less reported probably due to its tedious and time-consuming phenotyping (Atkinson & Wells, 2017;Burton, Williams, Lynch & Brown, 2012;Chopin, Laga, Huang, Heuer & Miklavcic, 2015;Uga, Okuno & Yano, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This method was used to investigate and understand the formation of emboli in saplings’ xylem during cycles from drought to re-watering [16]. The plant root formation in the soil is another research focus to utilize HRCT imaging and analysis [17-19]. This method enables scientists to trace the development of roots and foresee the plant’s growth status.…”
Section: Introductionmentioning
confidence: 99%